The creation and diffusion of knowledge - an agent based modelling approach - Emmanuel P. De Albuquerque (University College Dublin, UCD Centre for Economic Research, 2021)
In this paper I propose a novel abstract mechanism for the creation and diffusion of knowledge and use an agent based modelling approach to explore it. The mechanism takes into account the relation between the phenomena that agents attempt to explain and the stocks of knowledge available in a society, be it individually or collectively. I find that the aggregate number of knowledge units in a society increases more slowly, the more naive its inhabitants are. I also find that the proximity between phenomena plays an important role in how often the same knowledge unit can be used. A discussion on agent based models as a means of insight into society is offered.
Keywords: B52; C63; D83; O33; 330; Agent-based modelling; Cognitive distance; Exploitation; Exploration; Innovation; Knowledge creation; Knowledge diffusion; Learning